Characteristics prediction of insect chitin synthase - LU Jian-liang; LIN Chen; YANG Xiao-li; ZHENG Xin-qiang; LIANG Yue-rong (浙江大学学报. 农业与生命科学版)
According to the chitin synthase (CS) gene sequences deposited in GenBank, characteristics of insect CS were studied by software solution including GenDoc, PROSITE Motif search and PredictProtein. Eleven conserved domains at the amino acid sequence level, such as CAT (M/L) WHEX3 EMX3 LKSI, were found in insect CS. Ten of them were predicted in catalysis center which located inside of membrane and faced to cytoplast, the other one belonged to a coiled-coil region which located outside of membrane. Secondary structures were predicted that insect CS had high ratio of α helix and a compact shape. Additional transmembrane helixes were found in the C-terminal and N-terminal of insect CS comparing with the fungus. These helixes might be responsible for the transportation and localization of insect CS. It was also presumed that the coiled-coil region was the key domain for formation of CS high level structures and package of the new chitin strands.